Structural Mass Spectrometry of Membrane Proteins within Their Native Lipid Environments. Issue 51 (4th July 2018) - Reading, Eamonn
Abstract: Mass spectrometry has emerged as an important structural biology tool for understanding membrane protein structure, function, and dynamics. Generally, structural mass spectrometry of membrane proteins has been performed on purified or reconstituted systems which lack the native lipid membrane and cellular environments. However, there has been progress in the use and adaptations of these methods for probing membrane proteins within increasingly more native contexts. In this Concept article the use and utility of structural mass spectrometry techniques for studying membrane proteins within native environments are highlighted. Abstract : Natural behavior : Membrane proteins have evolved to perform their functions within the setting of a cell membrane. Structural mass spectrometry methods can explore the structure and dynamics of membrane proteins within their native cellular membrane environments.